2020
DOI: 10.1111/nph.16402
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of tomato fruit cuticles: a cross‐talk between the cutin polyester and cell wall polysaccharides

Abstract: Summary The cuticle is an essential and ubiquitous biological polymer composite covering aerial plant organs, whose structural component is the cutin polyester entangled with cell wall polysaccharides. The nature of the cutin‐embedded polysaccharides (CEPs) and their association with cutin polyester are still unresolved Using tomato fruit as a model, chemical and enzymatic pretreatments combined with biochemical and biophysical methods were developed to compare the fine structure of CEPs with that of the non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 87 publications
(118 reference statements)
3
76
1
Order By: Relevance
“…The cutin monomer batches contains 98 ± 0.5% of lipophilic compounds. The fatty acid composition of the lipophilic fraction was determined by gas chromatography coupled to a mass spectrometer as previously described 13 . A 60% yield of hydroxyfatty acids was obtained and the same batch of 500g of diOHC16 extract was used in the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cutin monomer batches contains 98 ± 0.5% of lipophilic compounds. The fatty acid composition of the lipophilic fraction was determined by gas chromatography coupled to a mass spectrometer as previously described 13 . A 60% yield of hydroxyfatty acids was obtained and the same batch of 500g of diOHC16 extract was used in the study.…”
Section: Methodsmentioning
confidence: 99%
“…All spectra (3 per co-polyester) were acquired in the 4000 to 700 cm -1 range at 4cm -1 resolution and accumulating 30 scans. 13 C solid state NMR (CP-MAS NMR) was carried out on a Bruker AvanceIII-400 MHz spectrometer operating at 100.61 MHz for 13 C, equipped with a double-resonance H/X CP-MAS 4-mm probe for CP-MAS (cross-polarization magic-angle-spinning) solid-state experiments. Sixty mg of the co-polyester films were put packed into 4 mm zirconia rotors.…”
Section: Structural Characterization Of the Cutin-like Co-polyester Fmentioning
confidence: 99%
“…The gradual increase in thickness of the noncutinized OEW during the later stages of development showed that polysaccharide material continued its deposition in the cell wall of the mutant, even after the control had reduced or stopped this process. These changes in the noncutinized OEW detected in the cus1-a mutant probably also affected its chemical composition, since it has recently been uncovered that the polysaccharide fraction of cus1-a cuticle displayed differences in pectin content (Philippe et al, 2020). These alterations in polysaccharide composition and OEW thickness could also explain the increase in epidermal cell size and altered shape of the cus1-a mutant, since a thicker OEW would be a limiting factor for growth and would sustain higher tensile stresses (Hamant and Traas, 2010).…”
Section: The Intimate Relationship Between the Cuticle And The Epidermentioning
confidence: 98%
“…In addition to changes in sugar content (Bret-Harte and Talbott, 1993), it is much thicker and less extensible than the rest of the cell walls (Kutschera, 2008). Recently, analysis of the polysaccharide domain of the tomato fruit cuticle has also shown chemical differences with the pericarp walls (Philippe et al, 2020). The clear reduction observed in the cus1-a mutant of both the cutinized and noncutinized fractions of the OEW at the onset of the expansion period indicates a relationship between CUS1 activity and cell wall development.…”
Section: The Intimate Relationship Between the Cuticle And The Epidermentioning
confidence: 99%
“…The cuticle is a composite material chiefly made of cutin, waxes (epicuticular and intracuticular waxes), and polysaccharides (Guzmán et al, 2014a,b;Fernández et al, 2017). Cutin is a polyester cross-linked by ester bonds of C16 and C18 hydroxy-fatty acids (Pollard et al, 2008;Fich et al, 2016); polysaccharides are found in the entire cuticle of leaves from different species (Guzmán et al, 2014a,b;Philippe et al, 2020). The outer cuticle surface is coated with a layer of epicuticular waxes (EWs) while intracuticular waxes (IWs) are embedded into the cuticle (Kulkarni et al, 2018).…”
Section: Introductionmentioning
confidence: 99%